FLASH sintering of porcelain stoneware: Effect of composition modifications. Issue 9 (August 2023) - Ribeiro, Camila; Figueiredo, Luis; Serrazina, Ricardo; Almeida, José C.; Salgado, Joana; Santos, Regina; Jorge, Hélio; Serrão, Álvaro; Marcos, Pedro; Costa, M. Elisabete; Vilarinho, Paula M.; Senos, Ana M.
Abstract: In this work, we have exploited FLASH sintering as an alternative sintering process in the production of porcelain stoneware. FLASH sintering of porcelain stoneware occurred at temperatures ∼ 1020 °C, for 500 V cm -1, 2 mA mm -2 in 30 s. These conditions are significantly less severe than those typically applied in its conventional sintering, 1150–1250 °C for 1 h. Despite the reduction of time and sintering temperature, FLASH sintered samples exhibit heterogeneous microstructure and elemental distribution, with localized glassy phase formed on the positive pole. By decreasing the feldspar content, less localized glassy phase and more uniform microstructures were obtained, being of relevance the highest density and microstructure uniformity attained in the composition without feldspar. These results extend the FLASH sintering applicability and illustrate its importance for the development of alternative sintering technologies in traditional ceramic industry, that in addition may benefit from the reduction of feldspar in the porcelain stoneware production.